A conserved oxalyl-coenzyme A decarboxylase in oxalate catabolism. (31st December 2022) - Cheng, Ninghui; Paris, Vincent; Rao, Xiaolan; Wang, Xiaoqiang; Nakata, Paul A.
ABSTRACT: The ability to biosynthesize oxalic acid can provide beneficial functions to plants; however, uncontrolled or prolonged exposure to this strong organic acid results in multiple physiological problems. Such problems include a disruption of membrane integrity, mitochondrial function, metal chelation, and free radical formation. Recent work suggests that a CoA-dependent pathway of oxalate catabolism plays a critical role in regulating tissue oxalate concentrations in plants. Although this CoA-dependent pathway of oxalate catabolism is important, large gaps in our knowledge of the enzymes catalyzing each step remain. Evidence that an oxalyl-CoA decarboxylase (OXC) catalyzes the second step in this pathway, accelerating the conversion of oxalyl-CoA to formyl-CoA, has been reported. Induction studies revealed that OXC gene expression was upregulated in response to an exogenous oxalate supply. Phylogenetic analysis indicates that OXCs are conserved across plant species. Evolutionarily the plant OXCs can be separated into dicot and monocot classes. Multiple sequence alignments and molecular modeling suggest that OXCs have similar functionality with three conserved domains, the N-terminal PYR domain, the middle R domain, and the C-terminal PP domain. Further study of this CoA-dependent pathway of oxalate degradation would benefit efforts to develop new strategies to improve the nutrition quality of crops.